Ecotoxicological effects of Linear Alkylbenzene Sulfonate on Biochemical Indices in Oreochromis niloticus Exposed Invitro - Thomas Ikpesu; Adenike Ariyo (Sustainable Earth Trends)
The anionic surfactant linear alkyl benzene sulfonate (LABS) is a synthetic surfactant, frequently utilized in domestic detergents as well as for a variety of industrial purposes. The effects of this ubiquitous pollutant on freshwater fish Orechromis niloticus were investigated. For 30 days, the fish were treated with the concentration ranges of LABS reported in the field (0.05,0.1,0.15, and 0.2) mg/L, including the control. Fish in both the control and experimental groups received twice-daily meals at 3% of their body weight throughout the experiment. A fish was removed from each plastic tub after each experimental period (2,9,16,23, and 30th) and was punctured in the heart to obtain blood samples. Blood was drawn and placed in sample bottles and analyzed for lipid peroxidation, aspartate aminotransferase, alanine aminotransferase, catalase, protein, and superoxide dismutase using standard methods. No deaths were noticed in either the control fish or the fish subjected to different sublethal concentrations of linear alkylbenzene sulfonate. After exposure to the surfactants, there was a noticeable alteration in the activities of the marker's indices in the blood of the fish. Tissue-specific, clear-cut time and dose dependence characterized the rate of changes in the assessed markers in the fish.